Disinfecting water mains (American Water Works Association, 2015)
This standard presents essential procedures for the disinfection of new and repaired potable water mains. Topics covered include forms of chlorine disinfection, a description of the disinfection procedure, preventive and corrective measures during construction, methods of chlorination, final flushing, bacteriological testing, redisinfection, final connections to existing mains, disinfection procedures when cutting into or repairing existing mains, and special procedures for caulked tapping sleeves. Appendixes cover chlorine residual testing, chlorine dosages, and disposal of heavily chlorinated water